THE INFLUENCE OF ORGANIZATIONAL CULTURE, WORK ENVIRONMENT AND COMMUNICATION ON EMPLOYEE JOB SATISFACTION AT PT LINGKAR ORGANIK INDONESIA - Lufiyanti, Dewi; Subiyanto, Didik; Purnamarini, Tri Ratna (LPPM Universitas Trunojoyo Madura, 2025)
The purpose of this study is to analyze: 1) The influence of organizational culture on employee job satisfaction at PT Lingkar Organik Indonesia, 2) The influence of the work environment on employee job satisfaction at PT Lingkar Organik Indonesia, 3) The influence of communication on employee job satisfaction at PT Lingkar Organik Indonesia. This type of research is quantitative research with a population of 54 employees, the sampling technique used is the saturated sample method. To ensure data quality, validity and reliability tests were carried out. Furthermore, the data obtained were analyzed through classical assumption tests, including normality tests, multicoloniality tests, and heterogeneity tests, as well as multiple linear regression analysis. Hypothesis testing was carried out using the t-test, f-test, and coefficient of determination (R²) test. The results of the study produced: 1) Organizational culture has a positive and significant effect on employee job satisfaction. 2) The work environment has a significant effect on employee job satisfaction. 3) Communication has a positive and significant effect on employee job satisfaction. Overall, organizational culture, work environment and communication simultaneously have a positive and significant effect on job satisfaction